Risk perceptions regarding radiation exposure among Japanese schoolteachers living around the Sendai Nuclear Power Plant after the Fukushima accident - Hori, Hiroko; Orita, Makiko; Taira, Yasuyuki; Kudo, Takashi; Takamura, Noboru (PloS one, 2019)
In response to the Fukushima Daiichi nuclear power plant disaster, the Nuclear Regulation Authority of Japan issued the new "Nuclear Emergency Response Guideline." However, there is a perception that scientific information about the health impact of radiation exposure has not been adequately shared among the local government staffs, including schoolteachers. We contacted schoolteachers at all 120 schools within the Urgent Protective Action Planning Zone of the Sendai Nuclear Power Plant, Kagoshima prefecture, in 2017. We invited them to take part in a written survey to clarify their concerns and risk perceptions regarding the effects of radiation exposure on health. Five hundred and fifty schoolteachers' replies were included in the analysis. The results revealed that 355 schoolteachers had concerns about the health effects of radiation exposure due to working within the Urgent Protective Action Planning Zone. A logistic regression analysis revealed that sex (OR = 2.26, 95% CI: 1.49-3.45, p < 0.001), age (OR = 3.39, 95% CI: 2.10-5.47, p < 0.001), reluctance to undergo a radiological examination at a hospital (OR = 1.91, 95% CI: 1.23-2.88, p = 0.004), place of work (OR = 2.18, 95% CI: 1.46-3.27, p < 0.001), and anxiety about having to address questions about radiation from students (OR = 4.66, 95% CI: 2.83-7.67, p < 0.001) were independently associated with schoolteachers' concerns about the health effects of radiation exposure due to working in the area around the nuclear power plant. Therefore, it is important to respond to these concerns in order to establish a meaningful education program for school children on radiation and its health effects.